A substituted sulfonamide and its Co (II), Cu (II), and Zn (II) complexes as potential antifungal agents. (2nd November 2016) - Diaz, Jorge R. A.; Fernández Baldo, Martín; Echeverría, Gustavo; Baldoni, Héctor; Vullo, Daniela; Soria, Delia B.; Supuran, Claudiu T.; Camí, Gerardo E.
Abstract: A sulfonamide 1-tosyl-1- H -benzo( d )imidazol-2-amine (TBZA) and three new complexes of Co(II), Cu(II), and Zn(II) have been synthesized. The compounds have been characterized by elemental analyses, FTIR, 1 H, and 13 C-NMR spectroscopy. The structure of the TBZA, and its Co(II) and Cu(II) complexes, was determined by X-ray diffraction methods. TBZA and its Co(II) complex crystallize in the triclinic P -1 space group, while the Cu(II) complex crystallizes in the monoclinic P21 /c space group. Antifungal activity was screened against eight pathogenic yeasts: Candida albicans (DMic 972576), Candida krusei (DMic 951705), Candida glabrata (DMic 982882), Candida tropicalis (DMic 982884), Candida dubliniensis (DMic 93695), Candida guilliermondii (DMic 021150), Cryptococcus neoformans (ATCC 24067), and Cryptococcus gattii (ATCC MYA-4561). Results on the inhibition of various human (h) CAs, hCA I, II, IV, VII, IX, and XII, and pathogenic beta and gamma CAs are also reported.